Anti-inflammatory activity of tinocrisposide by inhibiting nitric oxide production in lipopolysaccharides-stimulated raw 264.7 cells - Adnan, Adek Zamrud; Bakhtiar, Muhammad Taher; Afriani, Tika; ,, Annisa Fauzana; Roesma, Dewi Imelda; Putra, Andani Eka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to investigate in vitro anti-inflammatory activity of tinocrisposide using lipopolysaccharides (LPS)-stimulated RAW 264.7 macrophage cells. Tinocrisposide is a furano diterpene glycoside that was isolated in our previous study from Tinospora crispa. Methods: Anti-inflammatory effect was quantified spectrometrically using Griess method by measuring nitric oxide (NO) production after the addition of Griess reagent. Results: The sample concentrations of 1, 5, 25, 50, and 100 µM and 100 µM of dexamethasone (positive control) have been tested against the LPSstimulated RAW 264.7 cells, and the results showed NO level production of 39.23, 34.00, 28.9, 20.25, 16.3, and 13.68 µM, respectively, and the inhibition level of 22.67, 33.00, 43.03, 60.10, 68.00, and 73%, respectively. Conclusions: From the study, it could be concluded that tinocrisposide was able to inhibit the formation of NO in the LPS-stimulated RAW 264.7 cells in concentration activity-dependent manner, with half-maximal inhibition concentration 46.92 µM. It can be developed as anti-inflammatory candidate drug because NO is a reactive nitrogen species which is produced by NO synthase. The production of NO has been established as a mediator in inflammatory diseases.